2006
DOI: 10.1002/hup.810
|View full text |Cite
|
Sign up to set email alerts
|

Benztropine pretreatment does not affect responses to acute cocaine administration in human volunteers

Abstract: Benztropine (Cogentin ) was evaluated for its ability to block cocaine's physiological and subjective effects in humans. In healthy, recreational users of cocaine, placebo, or benztropine (1, 2, and 4 mg orally) was given 2 hr before subjects self-administered 0.9 mg/kg of cocaine intranasally. Measurements were made for 2 hr following cocaine administration, and plasma cocaine and cocaine metabolites were assayed. Cocaine produced typical increases in heart rate and alterations in self-reports measured by vis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 44 publications
2
9
0
Order By: Relevance
“…Cocaine significantly increased ratings of dissociation, psychedelic state, and feelings of vigor, friendliness, elation, positive mood, anxiety, and arousal, while decreasing fatigue. The effects on mood are in accordance with other studies also showing mood improvement following cocaine (Penetar et al, 2006; Rush et al, 1999; Walsh et al, 2009). Increased ratings of dissociation and psychedelic state following cocaine appear in line with studies reporting similar findings after administration of other stimulant drugs such as dexamphetamine and methylphenidate (Curran et al, 2004).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Cocaine significantly increased ratings of dissociation, psychedelic state, and feelings of vigor, friendliness, elation, positive mood, anxiety, and arousal, while decreasing fatigue. The effects on mood are in accordance with other studies also showing mood improvement following cocaine (Penetar et al, 2006; Rush et al, 1999; Walsh et al, 2009). Increased ratings of dissociation and psychedelic state following cocaine appear in line with studies reporting similar findings after administration of other stimulant drugs such as dexamphetamine and methylphenidate (Curran et al, 2004).…”
Section: Discussionsupporting
confidence: 92%
“…Although mood and psychedelic effects after cannabis administration have been extensively investigated (Battistella et al, 2013; D’Souza et al, 2008; Henquet et al, 2010; Lex et al, 1984; Ramaekers et al, 2006a; Toennes et al, 2008), there is a relative paucity in psychedelic subjective data after cocaine administration. It has been shown that cocaine administration has a stimulating effect on mood (Cascella et al, 1994; Penetar et al, 2006; Rush et al, 1999; Walsh et al, 2009), but these studies mainly measured general drug effects such as “feeling good” and “wanting to take again.” Also, although epidemiological evidence has associated extensive cocaine use with psychotic disorders (Morton, 1999; Roncero et al, 2012) and medication with a similar mechanism of action as cocaine, such as dexamphetamine and methylphenidate, has been shown to increase the likelihood of psychotic symptoms (Curran et al, 2004), no studies so far have investigated the acute effects of cocaine on measures of dissociation or psychedelic symptoms.…”
Section: Introductionmentioning
confidence: 99%
“…BZT is the only drug in its class approved for human use, due to its efficacy in early stages of PD, an effect thought to be due to its antimuscarinic effects. There is only one report in which BZT has been evaluated as a potential cocaine-abuse medication in humans (Penetar et al, 2006) in which 16 healthy recreational cocaine users were administered BZT (1, 2 or 4 mg) or placebo 2 hours before the subjects were allowed to self administer cocaine intranasally (0.9 mg/kg). Physiological and subjective measures of cocaine effects were monitored in the ensuing 2 hours.…”
Section: Behavioral Studiesmentioning
confidence: 99%
“…In a human laboratory study, Penetar and colleagues[80] examined the effects of the conjoint administration of cocaine with a mAChR antagonist, benztropine, in occasional cocaine users. Benztropine, an antimuscarinic and antihistamine medication, is commonly used to alleviate the extrapyramidal side effects (stiffness) from typical antipsychotics.…”
Section: Cholinergic System As a Target For Stimulant Addictionmentioning
confidence: 99%